Cuadro de mando integral para el control de la gestión en la Asociación de Mujeres Comunitarias del cantón Tosagua - Ordoñez Gilces, Yomaira Vanessa (2024)
The insufficiency in management control, the lack of a system of indicators, and the lack of standardized processes that cause economic losses in an organization, have led to the assumption as the main objective of the research, to design a comprehensive scorecard for management control of in the Association of Community Women in Tosagua canton. The methodology used was oriented under the quantitative approach with bibliographic and field research using the theoretical methods of deductive analysis-synthesis and meta-analysis, the data collection technique was the survey and the interview whose tool was the questionnaire whose validation was carried out with the expert method. Among the results, it was evident that the non-existence of alliances with international associations, the lack of awareness to improve cost efficiency, deficiency in customer retention, lack of knowledge about the usefulness of the marketing and distribution of products, little evaluation of the performance of workers and insufficient technological advances. It is concluded that there are evident difficulties due to the lack of use of tools for management control, as well as weaknesses in the coordination, planning and control of economic and administrative resources. Therefore, it is proposed to implement an action plan established according to the perspectives of the balanced scorecard.